2005
DOI: 10.1597/04-169
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of PTCH Gene Variants to Isolated Cleft Lip and Palate

Abstract: Objective-Mutations in patched (PTCH) cause the nevoid basal cell carcinoma syndrome (NBCCS), or Gorlin syndrome. Nevoid basal cell carcinoma syndrome may present with developmental anomalies, including rib and craniofacial abnormalities, and predisposes to several tumor types, including basal cell carcinoma and medulloblastoma. Cleft palate is found in 4% of individuals with nevoid basal cell carcinoma syndrome. Because there might be specific sequence alterations in PTCH that limit expression to orofacial cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 15 publications
1
31
0
1
Order By: Relevance
“…GLI2 is a member of the GLI-Kruppel family of zinc Wnger proteins and appears to be an obligatory mediator of Sonic Hedgehog (SHH) signaling pathway, which activates expression of the PTCH gene. Mansilla et al (2006) recently reported variants in PTCH showed evidence of linkage and disequilibrium with oral clefts in a sample of Filipino multiplex families.…”
mentioning
confidence: 96%
“…GLI2 is a member of the GLI-Kruppel family of zinc Wnger proteins and appears to be an obligatory mediator of Sonic Hedgehog (SHH) signaling pathway, which activates expression of the PTCH gene. Mansilla et al (2006) recently reported variants in PTCH showed evidence of linkage and disequilibrium with oral clefts in a sample of Filipino multiplex families.…”
mentioning
confidence: 96%
“…Gorlin syndrome for example is caused by mutations in PTCH and is associated with cleft palate in 5% of cases (Evans et al , 1993). Because of this association with clefts, PTCH was examined for mutations in cases of isolated CL/P (Mansilla et al , 2006). Two missense mutations were found in the extracellular loops of PTCH , predicted to interfere with SHH binding.…”
mentioning
confidence: 99%
“…Genome-wide linkage studies have revealed that the region 9q21 has significant linkage with facial clefting (Marazita et al, 2004). A number of candidate genes for CL/P in this region, 9q21–23, have been reported previously ( ROR2, PTCH, FOXE1 , and TGFBR1 ) (Ichikawa et al, 2006; Loeys et al, 2006; Mansilla et al, 2006; Mizuguchi et al, 2004; van Bokhoven et al, 2000; Vieira et al, 2005). Using a positional cloning approach, we demonstrated that SLC31A1 on chromosome 9 was disrupted within its intron.…”
Section: Discussionmentioning
confidence: 70%